SEJARAH PERKEMBANGAN GEREJA KATOLIK KRISTUS RAJA DI KOTA SAMBAS TAHUN 1980-2010 - Dennis Fofid; Yohanes Bahari; Haris Firmansyah (Universitas Tanjungpura, 2022)
Abstract The title of this research is “The History of the Development of the Catholic Church of Christ the King of Sambas City. The general problem in this research is how is the history of the development of the Catholic Church of Christ the King in Sambas City in 1980-2010 ?. The purpose of this study is to describe the development of the Catholic Church of Christ the King in Sambas City in 1980 – 2010. This study uses a historical methodology, namely topic selection, source selection (heuristics), source criticism (verification), interpretation, and historical writing (historiography). The approaches used in this research are social, economic, and geographical. The results of this study indicate that (1) The background of the establishment of the Catholic Church of Christ the King in Sambas City is the presence of missionaries to the city of Sambas in 1913, (2) The development of the Catholic Church of Christ the King of Sambas began when the Catholics in the city received testimonies from the people about the service of the death of the Church. Catholicism, the conversion of animists to religious adherents, (nuns, a Catholic social community in Sambas. Keywords: History of Development, The Catholic Church of Christ the King of Sambas.